God's gravediggers : why no deity exists - Bradley, Raymond D., 1931- (S.l. : Ockham Publishing, 2015)
Few can offer a more experienced view on religion than Ray Bradley. Having been raised as a 'winner of souls for Christ' in the 1940's, he spent the next 40 years as an atheist professor of philosophy and an outspoken critic /debater of religion. Revered for his work in logic and his meticulous approach to debate, God's Gravediggers is Bradley's coup de grâce to religion. A career's worth of work on a subject that could hardly be more important. Approaching the moral, logical and scientific arguments - using rich analogies, rational arguments and examples that non-academics would understand - he explores not only whether God exists, but also what damage the concept of God does